Glycogenic hepatopathy in a Korean girl with poorly controlled type 1 diabetes mellitus - Hwal Rim Jeong; Young Seok Shim; Young Bae Kim; Hae Sang Lee; Jin Soon Hwang (Korean Society of Pediatric Endocrinology, 2014)
Glycogenic hepatopathy (GH) is a rare complication of type 1 diabetes mellitus. We report the case of a 13-year-old diabetic female with poorly controlled blood sugar levels who presented with abdominal pain and distention 1 month in duration. She exhibited tender hepatomegaly, an elevated lipid profile, and elevated serum transaminase levels. Her liver histology was consistent with GH. The pathophysiology and/or underlying genetic background of GH remains unclear. The optimum treatment for GH is optimal glycemic control, and the prognosis is favorable. Clinicians should be aware of the possibility of GH and observe the clinical response to optimal glycemic control prior to invasive investigation.